FSI DRIVENERGY: MITIGATING SMARTPHONE ENERGY CONSUMPTION USING FUZZY INFERENCE - Ibrahim, Farid Iqbal; Md Nasir, Mohd Hairul Nizam; Ab Hamid, Siti Hafizah; Ahmad, Raja Wasim; Iqbal, Javed (Malaysian Journal of Computer Science, 2020)
Smartphones today help people accomplish daily activities, from simple tasks such as taking a reminder, to more complicated processes such as predicting road traffic while driving. However, performing complicated processes on smartphones cost the device’s energy to drain much faster. As an effect, the phone’s main purpose which is to enable communication whenever it is needed is degraded in terms of performance. In relation to this problem, researchers have tried to mitigate smartphone’s energy usage. An area that has yet to be further explored, is on examining smartphone’s context while the user is travelling. This paper presents a method to mitigate smartphone’s energy usage by gathering its context and to analyze it using Fuzzy Inference technique whilst the user is driving and using navigational application at the same time. Our finding shows that using this method can improve smartphone’s battery lifespan at an average rate, ranging between 1.6% to 3.1% for every hour with up to 19% of energy saving. These results proved that analyzing smartphone using context-awareness and Fuzzy Inference can reduce smartphone’s energy usage whilst the user is travelling, which in turn improves the overall energy efficiency in smartphone.